The first complete chloroplast genome of Fagopyrum leptopodum (Diels) Hedberg (Caryophyllales: Polygonaceae) with phylogenetic implications - Xueling Ye; Luo Wang; Dabing Xiang; Yanxia Sun (Mitochondrial DNA. Part B. Resources, 2021)
In the present study, we sequenced and assembled the complete chloroplast genome of Fagopyrum leptopodum (Diels) Hedberg. The chloroplast genome of F. leptopodum was composed of 85 protein-coding genes, 8 ribosomal RNA genes, and 37 transfer RNA genes. The F. leptopodum chloroplast genome is 159,375 bp in length, with a GC content of 37.81%. Phylogenetic analysis based on the combined chloroplast gene dataset indicated that the F. leptopodum exhibited a close relationship with Fagopyrum luojishanense.